Single-step rapid chromatographic purification and characterization of clinical stage oncolytic VSV-GP - Gautam, Saurabh; Xin, Dongyue; Garcia, Alan Pardo; Spiesschaert, Bart (Frontiers in Bioengineering and Biotechnology, 2022)
Purification of viruses, especially for therapeutic purposes, is a tedious and challenging task. The challenges arise due to the size and surface complexity of the virus particles. VSV-GP is a promising oncolytic virus, which has been approved for phase I clinical trials by the Food & Drug Administration (FDA) of U.S.A. and Paul Ehrlich Institute (PEI) of Germany. The virus particles of VSV-GP are larger in size than vectors commonly used for gene therapy (e.g., adenovirus, adeno-associated virus, etc.). The current established proprietary clinical-grade manufacturing process for the purification of VSV-GP encompasses several chromatographic and non-chromatographic steps. In this study, we describe a new single-step purification process for the purification of VSV-GP virus, using cation exchange convective flow column with relatively higher yields. The purified virus was characterized for its quality attributes using TCID50 assay (for viral infectivity), host cell protein contaminant ELISA, SDS-PAGE, size exclusion chromatography (SEC), and cryo-electron microscopy. Furthermore, the purified viral therapeutic material was tested in vivo for its efficacy and safety. All these characterization methods demonstrated a therapeutic virus preparation of high purity and yield, which can be readily used for various studies. The purification process can also be easily adopted for the variants of VSV and other similar viruses.